(untitled) (Research, Society and Development, 2021)
Purpose: This study disseminates the diagnosis of COVID-19 emphasizing the importance of imaging tests in medical interpretation and identification of its complications, besides demonstrating the contribution to patient care. Methodology: The study was conducted based on a literature review, in addition to the acquired results of imaging tests from clinical patients at a Public Hospital of the State of Sergipe, Brazil, to point the scoring system in thorax radiography and compare to computed tomography (CT). Results: The imaging tests are not indicated for patients with mild symptoms and suspected COVID-19 infection, except for risk of disease progression, being indicated in the complementary diagnosis of COVID-19 positive patients. Studies show that thorax radiography is more used because it has low cost and easy access. However, its use has limitations due to the low sharpness of the images and impossibility of visualization of some lesions. Computed tomography, on the other hand, can be used as a pulmonary monitoring and evolution test in patients with COVID-19 worsening and/or persistent homeostatic changes. Nevertheless, this test is not indicated for acute cases without aggravating symptoms. Conclusion: The high degree of dissemination of SARS-CoV-2 and the collapse of health systems demonstrated the importance of the science in health. In addition, the importance of laboratory tests in the diagnosis of virus infection and imaging tests in the early diagnosis of SARS-CoV-2 pneumonia has been shown as efficient complementarity in the evolution and clinical interpretation of patients, highlighting the importance of radiography and CT exams.